Poverty Alleviation Investment and Private Economy in China An Exploration of The Guangcai Programme - Wang, Lin.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book explores the mechanisms and significance of China$1 (Bs private economy participating in poverty alleviation. By basing its analysis on theories of development economics and public economics, the book stresses practical significance and abandons unreasonable assumptions. It uses a systematic set of statistical analysis tools and descriptive statistics to provide a multidimensional and highly visual format. Beyond the traditional qualitative comparison of countries, it also introduces quantitative comparison. Considering the increasing concern and curiosity about China$1 (Bs booming economy and rising private sector, the book is highly topical, offering readers theoretical insights into China$1 (Bs poverty alleviation mechanisms and essential information on the role played by the private economy in social and economic development.s
Preface -- Chapter I: The Development of the Guangcai Programme -- Chapter II: The Development of the Guangcai Programme -- Chapter III$1!+:(BTheoretical Structure of the Guangcai Programme -- Chapter IV$1!+:(BThe Guangcai Programme and the Poverty Alleviation Mechanism of NGOs -- Chapter V$1!+:(BThe Guangcai Programme and the Transformation of China's Poverty Alleviation -- Chapter VI$1!+:(BThe Guangcai Programme and Transformation of Poverty-Alleviation Model.s
Keywords: Economics; Economics/Management Science; Non-Profit Enterprises/Corporate Social Responsibility; Innovation/Technology Management; Organizational Studies, Economic Sociology